Intravenous zoledronate for postmenopausal women with osteopenia and osteoporosis: a systematic review and metanalysis - Gazon, Fernanda Martins; Civile, Vinicius Tassoni; Atallah, Álvaro Nagib; Santos, Fânia Cristina; Trevisani, Virginia Fernandes Moça (São Paulo Medical Journal, 2023)
BACKGROUND: Osteoporosis compromises bone strength and increases the risk of fractures. Zoledronate prevents loss of bone mass and reduces the risk of fractures. OBJECTIVES: To determine the efficacy and safety of zoledronate in postmenopausal women with osteopenia and osteoporosis. DESIGN AND SETTINGS: A systematic review and meta-analysis was conducted within the evidence-based health program at the Universidade Federal de São Paulo. METHODS: An electronic search of the CENTRAL, MEDLINE, Embase, and LILACS databases was performed until February 2022. Randomized controlled trials comparing zoledronate with placebo or other bisphosphonates were included. Standard methodological procedures were performed according to the Cochrane Handbook and the certainty of evidence for the Grading of Recommendations Assessment, Development, and Evaluation Working Group. Two authors assessed the risk of bias and extracted data on fractures, adverse events, bone turnover markers (BTM), and bone mineral density (BMD). RESULTS: Twelve trials from 6,652 records were included: nine compared zoledronate with placebo, two trials compared zoledronate with alendronate, and one trial compared zoledronate with ibandronate. Zoledronate reduced the incidence of fractures in osteoporotic [three years: morphometric vertebral fractures (relative risk, RR = 0.30 (95% confidence interval, CI: 0.24–0.38))] and osteopenic women [six years: morphometric vertebral fractures (RR = 0.39 (95%CI: 0.25–0.61))], increased incidence of post-dose symptoms [RR = 2.56 (95%CI: 1.80–3.65)], but not serious adverse events [RR = 0.97 (95%CI: 0.91–1.04)]. Zoledronate reduced BTM and increased BMD in osteoporotic and osteopenic women. CONCLUSION: This review supports the efficacy and safety of zoledronate in postmenopausal women with osteopenia for six years and osteoporosis for three years. PROSPERO REGISTRATION NUMBER: CRD42022309708, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=309708